An innovative micrometric granular graphite–glass system composite electrode “ready to use” in voltammetry techniques - Pierini, Gastón D. (2014)
Fil: Pierini, Gastón D. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca; Argentina